The pragmatics of propositional attitude reports - Jaszczolt, Katarzyna (Current research in the semantics/pragmatics interface, 2000)
This volume, the fourth in the Current Research in Semantics/Pragmatics Interface series, is a collection of nine papers dealing with the topic of reporting on beliefs and other attitudes, and in particular with the issue of the semantics-pragmatics boundary dispute which is the core topic of the current research in the field. Written by highly-regarded philosophers of language and linguists working on theoretical semantics and pragmatics, it brings together works in the mainstream tradition of logical form and the contextualism-anticontextualism debate and the research on the role of intentions, conventions, goals, plans and cultural stereotypes in attitude ascriptions. The editor's introductory chapter gives a valuable overview of the work, discussing the importance of all these aspects of propositional attitude research and stressing their compatibility and interdependence.